CLINICAL SIGNIFICANCE OF STUDYING GENETIC POLYMORPHISM OF THE Р450 CYP2C9 AND CYP2C19 DETOXIFYING ENZYME GENES IN EPILEPTIC CHILDREN - O. V. Guzeva; E. N. Imyanitov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: study of genetic polymorphism of the P450 CYP2C9 and CYP2C19 detoxifying enzyme genes in epileptic children. Study objective: to justify the effectiveness of therapy in children with severe forms of epilepsy by performing the genetic polymorphism analysis of the CYP2C9 and CYP2C19 detoxifying enzymes of the cytochrome P450 family. Materials and methods: a group of children with severe forms of epilepsy comprising 46 (53.49%) boys and 40 (46.51%) girls has been examined. Children were aged between 3 months and 17 years. Their epilepsy forms were diagnosed, the analysis of complications due to administration of anti-epileptic drugs (AED) was carried out and children with rare genotypes present in groups with both treatment resistant and non-resistant forms of epilepsy have been revealed. Results: the disease appeared to be treatment resistant in 56 (65.12%) of all children examined of whom 28 (50%) were boys and 28 (50%) were girls. Treatment resistant form of epilepsy was found in all (100%) children with epileptic encephalopathies and in 63.83% of children with symptomatic and cryptogenic focal epilepsy (with and without secondary generalization). 67 (77.91%) children received valproate monotherapy, 10 (11.63%) children received polytherapy that included valproates and 9 (10.47%) children received other AED. The non-resistant patients with idiopathic epilepsy more often developed complications during treatment with the AED. Gene polymorphism was found in 43 (50%) epileptic children, and in 36 (83.72%) cases rare genotypes were found in children with treatment resistant form of epilepsy and in 7 (16.28) cases in children with treatment non-resistant form of epilepsy. In children with polymorphic CYP2C9 and CYP2C19 genes the conventional average daily dose of valproates (30.56 mg/kg) exceeded the average daily dose of valproates (27.91 mg/kg) in children lacking the polymorphisms located in the same genes. Conclusion: we have revealed polymorphism in the CYP2C9 and CYP2C19 genes of the cytochrome P450 family in 50% of children with severe form of epilepsy, and in 41.86% of cases children with treatment resistant form of epilepsy had rare genotypes at that. Therefore, the results of genetic polymorphism analysis aiming to determine the presence or absence of polymorphic CYP2C9 and CYP2C19 genes should be taken into account before instigating treatment in children with epilepsy.